Gambaran Pengetahuan dan Tindakan Pegawai CIMB Niaga Cabang Manado tentang Dampak Penggunaan Komputer pada Kesehatan - Ratag, Gustaaf A.E.; Lampus, Benny S.; Wardoyo, Pingkan (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Improvement in working in an industry is barely seperated with computers. The use of computer can cause health problems, and are classified as occupational disease. Computer Vision Syndrome (CVS) is the form of occuler and non-occuler that occur after working with computer. According to survey in  America and England, 12.4% and 9% patient with CVS went to Hospital for an eye checked.2 Carpal Tunnel Syndrome (CTS) is one of syndrome that affect hand and has the higher potential to reduce everyday activity.4 The risk of being affected by CTS are more likely 10% for an adult, female has higher potential of being affected by CTS for 3 times more than male.5 This research are meant to analyze CIMB Bank’s worker about the cause of using computer for their health. The design of this research is descriptive and qualitive. The total informan that works using computer are counted as 20 workers. According to the research’s result, not every workers understood the side effect of using computer during work can affect their eyes. The same problem was found on the informan about the effect on using computer for their hand, less than half of the informan has no clue about the cause of using computer for their health. Keyword: Knowledge, action, employee, computer’s affect.